Investigation on the mechanical properties and durability of high performance concrete reinforced with waste tires fibers - REKIA ZOUINI; Abdelkadir Makani; Ahmed Tafraoui (The Journal of Engineering and Exact Sciences)
This paper aims to evaluate the mechanical behavior and durability of high-performance concrete reinforced with steel fibers recycled from waste car tires at 1% and 2% volume fractions and 2 cm and 3 cm lengths. Compressive and flexural strength tests were conducted on confined cubic and prismatic specimens at 28 days of age, with ultrasonic testing performed to confirm concrete properties non-destructively. Additionally, immersing specimens in 5% HCl and MgSO4 solutions to study their resistance in aggressive environments assessed the durability of the concrete.